PAI Teachers’ Strategy in Moral Development of Primary School Students - Nur Anisa; Murniyetti Murniyetti (Journal of Islamic Education Students, 2022)
This study aims to find out the strategies of PAI teachers in teaching moral values, growing awareness of moral values, monitoring students’ behavior, and having preventive and curative efforts against juvenile delinquency in primary schools. Descriptive qualitative method was used in this research. Techniques of data collections were interview, observation, and documentation. The data were analyzed by reducing data, displaying data, and drawing conclusion and verification. The result of this research described that there are two teachers’ strategies in teaching moral values to the primary students, namely lecture and discussion. While, in growing students’ awareness of moral values, teachers gave advices and familiarized the students with school regulations and routine programs. Next, teachers supervised the students directly and provided guidance for deviant behavior. Furthermore, to prevent juvenile delinquency, teachers supervised the students, communicated and collaborated with parents, and made regulations. Last, curative efforts were carried out by giving reward and punishment and facilitating a personal approach to the students.